Viability and Virulence of Fusarium oxysporum f. sp. zingiberi Isolates from Boyolali and Temanggung Preserved for 17 Years in Sterile Soils - Soesanto, Loekas; Fakhiroh, Zaqiatul; Suharti, Woro Sri (Jurnal Fitopatologi Indonesia, 2022)
Fusarium oxysporum f. sp. zingiberi is a soil-borne plant pathogen causing rhizome rot on ginger. This pathogen can survive in the soil for several years without a host plant. This study aimed to examine the viability and virulence of 21 isolates of F. oxysporum f. sp. zingiberi after being preserved for 17 years in sterile soil. Fungal viability was determined by descriptive method, while the experiment using randomized block design was conducted to examine the virulence of fungal isolates. The treatments consisted of control, 21 isolates of F. oxysporum f. sp. zingiberi from Boyolali and Temanggung, each treatment was replicated three times. The variables consisted of colony colors and diameters, macroconidia and microconidia shapes, growth time, dry weight of mycelia, conidia density, incubation period, affected area, rhizome wet weight difference, and waste index. The results showed that all fungal isolates which were stored in sterile soil for 17 years still had the ability to grow well on PDA medium and fill up petri dishes in 11–36 days. Moreover, all the isolates caused infection and disease symptoms development in ginger rhizome var. Gajah. Less virulence isolate was characterized by a long incubation period (6–12 days after inoculation) and smaller affected area of the rhizome.